Associations between cognitive activities and all-cause mortality among older adults with cognitive impairment: A prospective cohort study - Linjia Duan; Liming Zhao; Ziqiong Wang; Lu Liu; Ningying Song; Sen He (PLoS ONE, 2025)
Background Evidence on the association between cognitive activities and mortality among older adults with cognitive impairment is limited. Therefore, the study aimed to assess the association and examine whether baseline cognitive function mediates the association. Methods A total of 10477 older participants with cognitive impairment (median age: 95.0 [IQR: 88.0–100.0], males: 27.9%, Mini-Mental State Examination score ≤24 points) from the Chinese Longitudinal Healthy Longevity Survey conducted between 1998 and 2014 were included, with follow-up until 2018. Exposures were three prevalent cognitive activities among older adults in China: reading books/newspapers, playing cards/mah-jong, and watching TV or listening to radio, and the outcome was all-cause mortality within a 10-year follow-up period. We evaluated the association between these activities and mortality using Cox regression models and also conducted a mediation analysis to examine the role of baseline cognitive function in this association. Results During a follow-up period of totaling 33632.1 person-years, there were 8763 recorded deaths (83.6%). For each cognitive activity, the risk of mortality decreased with an increased frequency of engagement in these activities. Moreover, the risk of mortality significantly decreased with a greater number of cognitive activities. With zero activities as reference, adjusted hazard ratios were 0.83 (95% CI: 0.79–0.87) for one activity, 0.76 (95% CI: 0.69–0.83) for two activities, and 0.67 (95% CI: 0.53–0.86) for three activities, respectively. Stratified and sensitivity analyses confirmed the robustness of these findings. Additionally, baseline cognitive function partially mediated the association between cognitive activities and mortality; compared to zero activities, the mediated proportions were 15.2% (95% CI: 10.9%–22.4%) for one activity, 13.4% (95% CI: 8.9%–21.3%) for two activities, and 9.3% (95% CI: 4.2%–23.4%) for three activities, respectively. Conclusions Among older adults with cognitive impairment in China, the risk of all-cause mortality significantly decreased as both the frequency and number of cognitive activities increased. Baseline cognitive function only mediated a small proportion of the benefits of cognitive activities in longevity.